Optimization of the dietary protein and energy levels for Dhakai quail during growing period (Bangladesh Journal of Livestock Research, 2016)
A feeding trial was conducted to investigate the optimum level of dietary protein and energy on production performance and carcass characteristics of quail. A total number of 128 day-old chicks of Dhakai quail were used from internal hatchery of Bangladesh Livestock Research Institute, Savar, Dhaka. The chicks were arranged according to a 4 × 2 factorial (4 protein levels; 20, 22, 24 and 26% and 2 energy levels; 2800 and 2900 kcal ME/kg), and allocated into eight dietary treatment combinations according to the experimental design. The combinations were designated as D1 (CP20ME2800), D2 (CP20ME2900), D3 (CP22ME2800), D4 (CP22ME2900), D5 (P24ME2800), D6 (P24ME2900), D7 (P26ME2800) and D8 (P26ME2900). There were 16 chicks per treatment, each treatment had 2 replications having 8 chicks in each. At the end of 5 weeks, 2 birds from each replication were randomly selected and slaughtered to analyze the meat yield traits. All birds were fed ad libitum with treatment diets from day-old to 35 days of age. There were significant effect (P0.05). It was observed that the performance of Dhakai quail fed diet with 22% crude protein and 2900 kcal. ME/kg DM was better compared to others in terms of total gain, daily gain, FCR and dressing percent. Futher, treatments effect of protein level was observed on weight gain from day-old to 35 days. A crude protein level of 22.227% was estimated by regression equations for growing Dhakai quail.Bangladesh J. of Livestock Res. 19(1-2): 1-9, Jan-Dec 2012